Dispute Resolution of Double Land Sale and Purchase Deed - Fauzi, Harry (RESAM Jurnal Hukum, 2024)
The Deed of Land Deed Making Officer (PPAT) serves as a means of proving the truth of the sale and purchase, without being proven by the deed of the Land Deed Making Officer (PPAT) will not be able to obtain a certificate, even if the sale and purchase is valid according to law. The purpose of this research is to determine the legal strength of land ownership rights made before the PPAT and to find out the settlement of the land sale and purchase deed made before the PPAT with a double sale and purchase deed. This type of research is empirical juridical, by examining library materials which are secondary data and empirical legal research, namely research conducted by examining primary data. The results of this study show that the legal force of land ownership rights based on the sale and purchase deed made before the PPAT is an authentic deed that can be used as valid evidence of the existence of a sale and purchase transaction of freehold land. However, for strong proof of ownership of land can only be proven by the existence of a land certificate. Settlement of land sale and purchase deeds made before the PPAT with a double sale and purchase deed can be taken in 2 (two) ways, namely the first is taken by resolving disputes through mediation at the Land Office and by resolving disputes through the Court.